Pelatihan Penyusunan Artikel Ilmiah Bereputasi Dengan LaTeX Bagi Mahasiswa Indonesia di Malaysia - Ridho Ananda; Gushelmi Gushelmi; Maidawati Maidawati (LPPM IT Telkom Purwokerto, 2024)
The ability to write reputable article is an essential competency for academics and researchers. One of the requirements for an article to be said to be reputable is that it be published in a reputable international journal with a particular writing style. One of the writing styles presented is the LaTeX format. The advantages of this format, compared to others, are its stable, dynamic and efficient characteristics. In addition, LaTex is open source. Nevertheless, the implementation of the LaTeX format is not yet popular enough for certain groups, especially academics in Indonesia. Therefore, training was carried out in preparing reputable articles using LaTeX. This training is specifically for Indonesian students who are studying at Universiti Kebangsaan Malaysia based on their need. The training was held on May 4 2024 at 08.00 Malaysian standard time. The method used was teaching and discussing carried out online. Evaluation have been carried out based on the number of participants, formative test, and the participant responses. From the evaluation results, it is known that there were 31 participants. The average score on the formative test was 61.29. In addition, the dominant of participants strongly agreed with the usefulness of this training, where 16 (45.7%) participants giving positive comments. Meanwhile 10 (28.5%) participants provided suggestions, and the rest were neutral.